Model Pemetaan Kompetensi Pada Area TIK Menggunakan Sistem Informasi Berbasis Web - Bahar .; Soegiarto - STMIK Banjarbaru (Indonesian Journal of Networking and Security (IJNS), 2013)
Abstract - The lack of synchronization in the field of competency possessed by University graduates with those needed by the workforce (industry) to be one of the causes of many college graduates who are not absorbed by the (industrial) world. This condition is presumably because the education institution does not conduct the study of the competency needs of the world of work, or does not get sufficient information about the needs of the competence of the world of work as an important foundation in the design of instructional system (learning), so that basic competencies possessed by graduates of educational institutions are not relevant to the world of work . This article presents a model of Web-based information systems as a medium for synchronization (link and match) competency needs in ICT areas between work and educational institutions, especially in universities. This research begins by examining the basic competency needs of Information Technology for graduate user institution / institution as the basis for educational institution to design instructional, then analyzing and designing application of Web-based information system. The result of system model analysis and system architecture (System architecture and Information System Framework) is made to show the use of Web-based application system and Data Communication Technology Technology will be able to synchronize Instructional Products of ICT Study Program designed by Educational Institution with the need of work competence in industry ICT. Keywords: Web Based Information System, Competency Based Instructional, Information Technology Area, Educational Institution, Graduate User Abstrak - Tidak sinkronnya bidang kompetensi yang dimiliki oleh lulusan Perguruan Tinggi dengan yang dibutuhkan oleh dunia kerja (industri) menjadi salah satu penyebab banyaknya lulusan perguruan tinggi yang tidak terserap oleh dunia kerja (industri). Kondisi ini diduga karena institusi pendidikan tidak melakukan kajian kebutuhan kompetensi dunia kerja, atau tidak mendapatkan informasi yang memadai mengenai kebutuhan kompetensi dunia kerja sebagai landasan penting dalam mendesain sistem instruksional (pembelajaran), sehingga kompetensi dasar yang dimiliki oleh lulusan institusi pendidikan tidak relevan dengan dunia kerja. Artikel ini menyajikan model sistem informasi berbasis Web sebagai media untuk sinkronisasi (link and match) kebutuhan kompetensi pada area TIK antar dunia kerja dengan Institusi pendidikan, khususnya di Perguruan Tinggi. Penelitian ini diawali dengan mengkaji kebutuhan kompetensi dasar bidang Teknologi Informasi bagi instansi/institusi pengguna lulusan sebagai dasar bagi institusi pendidikan untuk mendesain instruksional (pembelajaran), selanjutnya menganalisis dan membuat desain aplikasi sistem informasi berbasis Web. Hasil analisis model/desain sistem (arsitektur sistem dan Framework Sistem Informasi) yang dibuat menunjukkan penggunaan sistem aplikasi berbasis Web dan Teknologi Jaringan Komunikasi Data akan dapat mengsinkronkan Produk Instruksional Program Studi TIK yang dirancang oleh Institusi Pendidikan dengan kebutuhan kompetensi dunia kerja (industri) pada area TIK. Kata Kunci : Sistem Informasi Berbasis Web, Instruksional Berbasis Kompetensi, Area Teknologi Informasi, Institusi Pendidikan, Pengguna Lulusan